FRACTIONATION TRENDS AMONG IVA IRON METEORITES: CONTRASTS WITH IIIAB TRENDS - Wasson J.T.; Richardson J.W. (My University, 2001)
A neutron-activation study of 48 group-IVA irons shows much lower negative slopes on Ir-Au and Ir-As diagrams than observed in the larger magmatic group IIIAB. This difference seems to reflect the tendency of DIr, DAu and DAs to increase with increasing S content. Contents of S and other volatiles are much lower in IVA irons than IIIAB irons. We show that both groups can be fit with DX values that depend quadratically on S, with initial IVA S contents about 6X lower than those in IIIAB. The IVA scatter fields show a spread in Au or As at constant Ir that appears to reflect variations in the fraction of trapped melt between 0% and 30%. Copper shows an S-shaped trend that may reflect moderate positive and negative changes in DCu as the magma evolved or, less likely, sampling variations in a broad band reflecting fractionation and trapping of melt. Gibeon, the largest IVA iron with a mass > 30 tons, shows an appreciable range in compositions consistent either with differences in the degree of magma crystallization or with differences in the content of trapped melt. A striking difference between IVA and IIIAB is observed in the Ir/Au ratios in the most Ir-rich irons in the groups; that in IVA is 40% lower than the IIIAB ratio, and lower than those in other iron-meteorite groups. The IVA Ir/Au ratio is about half the ratios in the chondrite groups. We examined three possible explanations of this anomaly: (1) the high-Ir irons contain large amounts of trapped melt; or (2) half of the IVA core (i.e., the first 50% to crystallize) is missing from the terrestrial set of IVA irons; or (3) the IVA magma formed by incomplete melting of the metal in the chondritic precursor material, with the metal that remained in the mantle having high Ir and low Au contents. Plausibility arguments favor the third possibility. The third scenario is the most plausible, but the second cannot be ruled out. We review recent evidence regarding the cooling rates in group IVA. In contrast to recent interpretations, we note several lines of evidence that indicate constant cooling rates independent of composition, as expected if all IVA meteorites were in the same core when cooling between 900 and 650 K occurred.